A patient‐specific aperture system with an energy absorber for spot scanning proton beams: Verification for clinical application. Issue 12 (13th November 2015) - Yasui, Keisuke; Toshito, Toshiyuki; Omachi, Chihiro; Kibe, Yoshiaki; Hayashi, Kensuke; Shibata, Hiroki; Tanaka, Kenichiro; Nikawa, Eiki; Asai, Kumiko; Shimomura, Akira; Kinou, Hideto; Isoyama, Shigeru; et al.
Abstract : Purpose: In the authors' proton therapy system, the patient‐specific aperture can be attached to the nozzle of spot scanning beams to shape an irradiation field and reduce lateral fall‐off. The authors herein verified this system for clinical application. Methods: The authors prepared four types of patient‐specific aperture systems equipped with an energy absorber to irradiate shallow regions less than 4 g/cm 2 . The aperture was made of 3‐cm‐thick brass and the maximum water equivalent penetration to be used with this system was estimated to be 15 g/cm 2 . The authors measured in‐air lateral profiles at the isocenter plane and integral depth doses with the energy absorber. All input data were obtained by the Monte Carlo calculation, and its parameters were tuned to reproduce measurements. The fluence of single spots in water was modeled as a triple Gaussian function and the dose distribution was calculated using a fluence dose model. The authors compared in‐air and in‐water lateral profiles and depth doses between calculations and measurements for various apertures of square, half, and U‐shaped fields. The absolute doses and dose distributions with the aperture were then validated by patient‐specific quality assurance. Measured data were obtained by various chambers and a 2D ion chamber detector array. Results: The patient‐specific aperture reduced the penumbra from 30% to 70%, for example, from 34.0 to 23.6 mm and 18.8 to 5.6 mm. The calculated field width for square‐shaped apertures agreed with measurements within 1 mm. Regarding patient‐specific aperture plans, calculated and measured doses agreed within −0.06% ± 0.63% (mean ± SD) and 97.1% points passed the 2%‐dose/2 mm‐distance criteria of the γ ‐index on average. Conclusions: The patient‐specific aperture system improved dose distributions, particularly in shallow‐region plans.